1998
DOI: 10.1152/jappl.1998.85.2.418
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and performance responses during endurance exercise after high-fat and high-carbohydrate meals

Abstract: We studied the effects of preexercise meal composition on metabolic and performance-related variables during endurance exercise. Eight well-trained cyclists (maximal oxygen uptake 65.0 to 83.5 ml . kg-1 . min-1) were studied on three occasions after an overnight fast. They were given isoenergetic meals containing carbohydrate (CHO), protein (P), and fat (F) in the following amounts (g/70 kg body wt): high-carbohydrate meal, 215 CHO, 26 P, 3 F; high-fat meal, 50 CHO, 14 P, 80 F. On the third occasion subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
53
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 36 publications
8
53
3
1
Order By: Relevance
“…Montain et al [ 19 ] showed that despite similar postprandial insulin concentrations 4 h prior to exercise compared to 12 h postprandially there was a diff erence in CHO oxidation and fat metabolites between conditions, supporting a long lasting eff ect of insulin. Consistent with the current investigation Whitley et al [ 28 ] reported no significant diff erences in insulin concentrations following the consumption of either a HFM or HCM during exercise. However, again insulin was not analysed postprandially so similar caveats to the present investigations may be warranted.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Montain et al [ 19 ] showed that despite similar postprandial insulin concentrations 4 h prior to exercise compared to 12 h postprandially there was a diff erence in CHO oxidation and fat metabolites between conditions, supporting a long lasting eff ect of insulin. Consistent with the current investigation Whitley et al [ 28 ] reported no significant diff erences in insulin concentrations following the consumption of either a HFM or HCM during exercise. However, again insulin was not analysed postprandially so similar caveats to the present investigations may be warranted.…”
supporting
confidence: 91%
“…These fi ndings suggest that the type of meal ingested prior to soccer simulated exercise has an impact on metabolism, but not on the subsequent performance as determined in the present study. no improvements in performance for a cycling capacity test [ 21 , 22 ] or for time trial performance [ 28 ] , critically these studies demonstrate no performance decrements. Underlying these observations is the principle that a HFM enables an increase in fatty acids (FA) availability during the postprandial period and onset of exercise, an increase in the rate of fat oxidation resulting in a matched or enhanced performance.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…An increase in plasma free fatty acid (FFA) and fat oxidation has been shown to spare endogenous glycogen, most reliably via fat infusion studies (38). However, fat infusion during racing conditions is not feasible, and long-chain triglyceride ingestion before or during exercise has not been shown to enhance performance (14,32,40). More recently, interest has focused on the ingestion of medium-chain triglycerides (MCTs).…”
mentioning
confidence: 99%